Distributional range extension of Lutjanus arakan Hasan, Durand & Iwatsuki 2025 (Perciformes: Lutjanidae) from the Indian coast - Behera, Rajesh Kumar; Mohanty, Swarup Ranjan; Acharya, Smrutirekha; Thathachari, T K S; Behera, Bhaskar; Mishra, Subhrendu Sekhar; Mohapatra, Anil (Zootaxa, 2026)
The present study provides evidence of Lutjanus arakan Hasan, Durand & Iwatsuki 2025 from Indian waters, based on a specimen collected from the Gopalpur coast, Odisha. The combination of distinct colouration, meristic counts, and genetic simillarities provides strong evidence supporting the recognition of Lutjanus arakan from the Indian Ocean.